2016
DOI: 10.1080/1745039x.2016.1141743
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of high levels of vegetal proteins in diets for market-sized gilthead sea bream (Sparus aurata)

Abstract: Monge-Ortiz, R.; Martínez-Llorens, S.; Marquez, L.; Moyano-Lopez, FJ.; Jover Cerda, M.; Tomas-Vidal, A. (2016). Potential use of high levels of vegetal proteins in diets for marketsized gilthead sea bream (Sparus aurata). Archives of Animal Nutrition. 70 (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 36 publications
7
27
1
Order By: Relevance
“…In last decades, many studies have been conducted to investigate the use of plant origin feed additives in fish diets due to the residual problems of synthetic feed additives or substitution of fishmeal as protein sources (Monge‐Ortiz et al, ; Nogales‐Mérida, Tomás‐Vidal, Moñino‐López, & Martínez‐Llorens, ). The main aim of these studies was to improve the growth performance of fish and to turn the negative effects of synthetic products such as antibiotics into benefits with plant‐based additives (Baba, Acar, Öntaş, Kesbiç, & Yilmaz, ; Acar et al, ; Parrino, Kesbiç, Acar and Fazio, [In press], Kesbiç & Yigit, ).…”
Section: Discussionmentioning
confidence: 99%
“…In last decades, many studies have been conducted to investigate the use of plant origin feed additives in fish diets due to the residual problems of synthetic feed additives or substitution of fishmeal as protein sources (Monge‐Ortiz et al, ; Nogales‐Mérida, Tomás‐Vidal, Moñino‐López, & Martínez‐Llorens, ). The main aim of these studies was to improve the growth performance of fish and to turn the negative effects of synthetic products such as antibiotics into benefits with plant‐based additives (Baba, Acar, Öntaş, Kesbiç, & Yilmaz, ; Acar et al, ; Parrino, Kesbiç, Acar and Fazio, [In press], Kesbiç & Yigit, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant protein origins have advantages in price, stable supply, and nutritional composition (Daniel, 2018;Gatlin et al, 2007). A wide range of plant protein ingredients such as soybean (Murashita et al, 2018;Ye et al, 2019;Zhang et al, 2018), corn gluten (Gerile & Pirhonen, 2017), corn-protein concentrate (Ng, Leow, & Yossa, 2019), wheat gluten (Monge-Ortiz et al, 2016), rapeseed (Dossou et al, 2018), peas (Nogales-Mérida, Tomás-Vidal, Moñino-López, Jover-Cerdá, & Martínez-Llorens, 2016), canola (Thiessen, Maenz, Newkirk, Classen, & Drew, 2004), cottonseed (Pham et al, 2008;Pham, Lee, Lim, & Park, 2007), and rice distillers' dried grain (Bae, Kim, & Lee, 2015) have been explored as FM alternatives in aquafeed. However, the presence of antinutritional factors or nutritional imbalance in the plant proteins that might negatively affect fish growth, gut microbiota composition, immune response, and survivability (Desai et al, 2012;Liang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with single protein source, blending protein sources can balance amino acid profile, reduce price and improve palatability, as well as reduce indigestible carbohydrate, antinutritional and toxic factors (Bulbul, Koshio, Ishikawa, Yokoyama, & Kader, ; de Francesco et al, ). Thus, high FM substitution level could be achieved by mixture of protein sources (Monge‐Ortiz et al, , ). Zhang, Øverland, Xie, et al () found that mixture of lupin and pea protein concentrates can efficiently replace FM for black sea bream.…”
Section: Introductionmentioning
confidence: 99%